2004
DOI: 10.1111/j.1471-4159.2004.02681.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Naphthoflavone disturbs astrocytic differentiation of C6 glioma cells by inhibiting autocrine interleukin‐6

Abstract: Regulation of astrocyte differentiation is a key process in the development of the central nervous system (CNS), and disturbance of the differentiation can lead to brain system dysfunction. Here we show that b-naphthoflavone (bNF), an agonist of the aryl hydrocarbon receptor (AhR), disturbed the cAMP-induced astrocytic differentiation of C6 glioma by inhibiting autocrine interleukin-6 (IL-6). Treatment of cells with bNF reduced the induction of an astrocyte marker glial fibrillary acidic protein (GFAP). This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Furthermore, it is well established that GFAP is not only a reliable marker for gliogenesis but also works as a tumor suppressor gene in malignant glioma pathogenesis (Duffy et al., 1982; Rutka et al., 1994; Rutka and Smith, 1993). Therefore, our findings support those previous reports demonstrating that proinflammatory cytokines might work as potential differentiation‐supporting agents against malignant gliomas (Koch et al., 2007; Slegers and Joniau, 1996; Takanaga et al., 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, it is well established that GFAP is not only a reliable marker for gliogenesis but also works as a tumor suppressor gene in malignant glioma pathogenesis (Duffy et al., 1982; Rutka et al., 1994; Rutka and Smith, 1993). Therefore, our findings support those previous reports demonstrating that proinflammatory cytokines might work as potential differentiation‐supporting agents against malignant gliomas (Koch et al., 2007; Slegers and Joniau, 1996; Takanaga et al., 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Interleukin-6 (IL-6)-type cytokines are major regulators of inflammation and thereby contribute to the neuropathology and pathophysiology associated with inflammation of the central nervous system (CNS) (Koch et al, 2007). Furthermore, it is well established that GFAP is not only a reliable marker for gliogenesis but also works as a tumor suppressor gene in malignant glioma pathogenesis (Duffy et al, 1982;Rutka et al, 1994;Rutka and Smith, 1993).Therefore, our findings support those previous reports demonstrating that proinflammatory cytokines might work as potential differentiation-supporting agents against malignant gliomas (Koch et al, 2007;Slegers and Joniau, 1996;Takanaga et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Previous evidences showed that STAT3 activation regulated downstream genes by AhR ligands including TCDD ( 45 ), indoxyl sulfate ( 46 ), and β-naphthoflavone ( 47 ). However, the current results showed that ligand-independent activation of AhR could efficiently mobilize LPS-stimulated STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…33 In another study, inhibition of IL-6 by the AhR agonist ␤-naphthoflavone in C6 glioma cells was demonstrated, leading to a block in astrocyte differentiation for which IL-6 is an important autocrine factor. 34 Given the complex biology of the AhR, several scenarios can be envisioned to explain the mode of action of VAF347 on DC to inhibit IL-6 production. One possibility is the presence of negatively acting AhR binding sites in the IL-6 promoter.…”
Section: Discussionmentioning
confidence: 99%